PENERAPAN METODE BALANCED SCORECARD SEBAGAI TOLOK UKUR PENGUKURAN KINERJA PERUSAHAAN - Nugrahayu, Erika Ributari; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to identify and to analyze the application of the balanced scorecard method as the standard measurement of performance at PT Glory Indonesia Abadi. The method of research is qualitative method, since this research is not meant to prove a hypothesis but it is meant to disclose facts and condition that occurs in the research. The discussion has showed that the balanced scorecard method which interprets the vision, mission and strategy into performance assessment that has four indicators, i.e. the financial perspective which indicate the fluctuate figures, the customer perspective show quite good results, internal business process perspective shows that the company has made some innovation processes i.e. recycle the raw material of paper into newspapers and produce various color HVS paper and service availability to meet the customer demand in urgent time, growth and learning perspective show good performance condition because it can improve the quality of its employees. It can be concluded from the above discussion that the use of balanced scorecard method can be used as the standard for the success of a company. In order to the balanced scorecard method can be applied on the company, some improvement efforts are needed both internal and external aspect.Keywords: Performance Assessment, Balanced Scorecard, Balanced Scorecard Perspective.